The nucleotide sequence of the bovine interleukin-5-encoding cDNA - Mertens, B.; Gobright, E.I.; Seow, H.F. (Elsevier, 1996)
The nucleotide (nt) sequence encoding the bovine homologue of interleukin-5 (boIL-5) was determined. Total cDNA generated from stimulated bovine peripheral blood lymphocytes was used to amplify the boIL-5 gene using primers based on the 5' and 3' untranslated regions of the ovine IL-5 cDNA sequence. The boIL-5 coding sequence is 405 by long, coding for a 15.2 kDa precursor protein of 134 amino acids (aa). Cleavage of a putative signal peptide of 19 aa yields a mature form of 13.1 kDa. Comparisons at the nt level revealed 96%, 81%, 74% and 73% identity with the ovine, human, mouse and rat IL-5 sequences, respectively, and 97%, 66%, 59% and 58% aa identity, respectively.